Gendered patterns in the associations between in-school physical activity, classroom peer ecology, and academic achievement among primary school students - Anni Byman; Sanna Ulmanen; Kirsi Pyhältö; Heidi Syväoja; Janne Kulmala; Tuija H. Tammelin (PLoS ONE, 2026)
School is an important setting for increasing students’ engagement in physical activity (PA) and reducing sedentary time (ST), both of which are linked to health and academic achievement. Peer interactions within the classroom can influence students’ engagement in PA and sedentary behaviors during the school day, yet research on how classroom peer ecology relates to objectively measured in-school PA and ST is limited. Even less is known about gender differences in these associations. The objective of this study was to examine how students’ perceived classroom peer ecology is associated with in-school PA and ST and how these factors relate to academic achievement. Gendered patterns in these dynamics were also explored. A sample of 517 Finnish primary school students (53% girls, 47% boys, M age = 11.6 years, SD age = 0.9 years) participated in this cross-sectional study in 2013. Students’ perceptions of classroom peer ecology were investigated through a survey. Moderate-to-vigorous PA (MVPA) and ST during school hours were measured by hip-worn accelerometers. Grade point averages (GPA) were calculated based on subject grades. Associations were investigated through multigroup structural equation modeling analyses. In girls, positive classroom peer relations were associated with lower in-school MVPA, while greater in-school ST was linked to higher GPA. Among boys, higher in-school MVPA was related to higher GPA. Although the MVPA-related associations differed in statistical significance across groups, subsequent formal tests did not indicate statistically significant gender differences, and hence further studies are needed on the subgroup-specific patterns to confirm or invalidate the findings. Efforts to promote a physically active school day could benefit from considering how activity opportunities are experienced within peer dynamics and in relation to gender, including the need for socially inclusive approaches.